Design and evaluation of slow sand and UV filters for effective nutrient recycling in closed soilless cultivation - SINGH, KAMAL GURMIT; SINGH, ANGREJ; SHAH, AAMIR ISHAQ; SINGH, GURPARTEET (The Indian Journal of Agricultural Sciences, 2024)
Nutrient and water use efficiency can be improved in soilless cultivation systems by recirculating the leachate. However, untreated leachate contains particulate matter that may clog drip emitters and root pathogens which can pose a threat to the crop health if reintroduced into the system. To address this issue, an ultraviolet (UV) filter was developed to complement the slow sand filter to enhance its treatment efficiency in removing root pathogens. The experiment was conducted during 2019 and 2020 at Punjab Agicultural University, Ludhiana, Punjab to assess the effectiveness of the UV filter in removing pathogens, specifically Dickey zeae and Xanthomonas, from the leachate in a closed soilless cultivation system. Pre and post-treatment measurements were made 40 days after transplanting (DAT) and 80 DAT to evaluate the efficiency of the UV filter. The results revealed that combined UV and slow sand filters substantially treated the raw leachate. At 40 DAT, the pathogen removal efficiency was 94.8%, while it was 92% at 80 DAT. The findings highlight the importance and effectiveness of using the UV filter as an additional treatment step in closed soilless cultivation systems with significant improvement in the overall removal efficiency of root pathogens from the leachate.